Fostering EFL Students’ Critical Thinking Skills in Differentiating Between Factual and Fake News (Gunung Djati Conference Series, 2025)
This study intends to evaluate students' critical thinking (CT) skills after being taught aboutCT. The evaluation focuses on three core CT competencies: identification, identifyingbiases, and inference (Erstad in Fatiha et al., 2021). Data were collected through 36 studentanswers based on CT questions on news analysis material in reading class. This researchadopted a descriptive analysis method to assess and categorize students' CT abilities basedon high, middle, and low levels. A modified version of NEIU's CT rubric was utilized forassessment. The results indicated that 67% of students achieved a high level, 28% achieveda middle level, and 5% fell into the low category. Students at the high level succeeded inapplying all three core CT skills. In addition, students at the middle level succeeded inapplying two CT core skills, and those with low ability could only demonstrate one CT coreskill. Hence, The study presents an alternate framework for instructing CT.